Oil Prices Dynamics and the State of Energy Crisis in Pakistan - Hussain, Jibran; Hassan, Sallahuddin (Pakistan Journal of Humanities and Social Sciences, 2019)
The dependence on non-renewable energy sources is the key factor controlling international oil prices, geoeconomics, geopolitical and geostrategic relations, business and macroeconomic dynamics. The developing economies remain volatile to oil price due to their heavy reliance on non-renewable energy sources and their low capability to maintain stable energy stock, such as Pakistan. The existing weak, unstable energy system has not been able to devour the frequent blows of oil price volatilize and shocks over the years and have been provoking energy crisis in the country. The application of vector error correction mechanism shows a statistically significant positive impact of oil prices on the energy crisis in the long run as well as in the short run.